Methodological issues in assessing the incidence of peritoneal dialysis-associated peritonitis in children - Schaefer, Franz; Kandert, Marianne; Feneberg, Reinhard (Peritoneal dialysis international, 2002)
To evaluate the distribution of peritonitis incidence and assess the usefulness of patient-specific peritonitis rates in children.? Design49 children on automated peritoneal dialysis (PD) followed during a 2-year observation period.
Gesehen am 22.01.2021